Good Governance in Islam: Classical and Contemporary Approaches (American Journal of Islam and Society, 2012)
The Summer Institute for Scholars 2012, held at the IIIT headquarters in Herndon,VA, from July 9-18, 2012, brought together twenty scholars to address“Good Governance in Islam: Classical and Contemporary Approaches.” Inorder to present as many of their ideas as possible, the wide-ranging andthought-provoking comments of the chairs and the discussants are not recountedhere ...